Initiation and evolution of phase separation in GaP/InP short-period superlattices - Shin, B; Chen, W; Goldman, RS; Song, JD; Kim, JM; Lee, YT (A V S AMER INST PHYSICS, 2004)
We have investigated the initiation and evolution of lateral phase separation in GaP/InP short-period superlattices (SPSs). Cross-sectional scanning tunneling microscopy reveals lateral contrast modulations within the SPS region, presumably due to alloy phase separation. The wavelength of the modulations appears to be constant throughout the entire SPS structure. Interestingly, the wavelength is dependent on the thickness of the constituent layers of the superlattice, and is likely to be affected by an observed significant concentration of group V vacancies. Together, these results suggest that phase separation is initiated by compositional nonuniformities from excess surface adatoms due to incomplete coverage of the constituent layers of the superlattice, and that the phase separation process is assisted by In-Ga interdiffusion via P vacancies. (C) 2004 American Vacuum Society.
Keywords: LATERAL COMPOSITION MODULATION; WURTZITE TYPE SEMICONDUCTORS; MOLECULAR-BEAM EPITAXY; LAYER ORDERING PROCESS; VIRTUAL-ENTHALPIES; ANION VACANCIES; ZINCBLENDE; RELAXATION; SURFACES; INP(110)